2015
DOI: 10.1017/s1751731114003267
|View full text |Cite
|
Sign up to set email alerts
|

Effects of sequential feeding with low- and high-protein diets on growth performances and plasma metabolite levels in geese

Abstract: This study was conducted by two trials to investigate effects of sequential feeding with low-and high-protein diets on growth traits and plasma metabolites in geese. In Trial I, the effect of sequential feeding under time-restricted feeding system was investigated. Seventy-two White Roman goslings were randomly allotted into either sequential feeding (S1) or control feeding (C1) group. All goslings were fed for 1 h at morning and at evening, respectively, from 2 to 8 weeks of age. S1 group was offered 13% CP d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 19 publications
0
2
0
Order By: Relevance
“…Therefore, how the intestinal development and the gut constituent shaped the herbivority of geese fascinated researchers. Previous studies indicated the geese could also be reared like chickens with high-concentrate diets ( 18 ), and the growth performances changed with different nutritional levels ( 19 , 20 ). Whereas, the geese gut microbiota profiles and their interactions with epithelial cells are still of limited cognition.…”
Section: Discussionmentioning
confidence: 99%
“…Therefore, how the intestinal development and the gut constituent shaped the herbivority of geese fascinated researchers. Previous studies indicated the geese could also be reared like chickens with high-concentrate diets ( 18 ), and the growth performances changed with different nutritional levels ( 19 , 20 ). Whereas, the geese gut microbiota profiles and their interactions with epithelial cells are still of limited cognition.…”
Section: Discussionmentioning
confidence: 99%
“…As feed represents a large part of the cost of pig production and the energy component represents the greatest proportion of feed cost (Noblet, 2007;Velayudhan et al, 2015), the SEQ feeding program may be economically advantageous than the HF/ LP program since SEQ pigs had the best values for energy cost of gain and NE intake in the growing 2 and finishing phases, respectively. Accordingly, sequential feeding with low and high-protein diets improved the weight gain (10%) and feed efficiency (8%) in growing geese exposed to ambient temperature variations between 22°C and 29°C (Ho et al, 2015). In contrast, no effect of sequential feeding with diets varying in CP and energy content was observed in male broilers reared at a constant ambient temperature of 37°C (Bouvarel et al, 2004).…”
Section: Effect Of Hf/low-crude Protein Sequential Feeding On Pig Performance and Body Compositionmentioning
confidence: 94%